Supplemental Zinc Sulfate Interacts with Optaflexx in Feedlot Heifers - C. L. Van Bibber-Krueger; R. G. Amachawadi; H. M. Scott; J. M. Gonzalez; J. S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2017)
Optaflexx is a beta-adrenergic agonist, and is fed to cattle during the final 28 to 42 days on feed to improve growth rate and feed efficiency. Beta-adrenergic agonists are repartitioning agents that stimulate muscle deposition at the expense of fat deposition. Zinc is a trace mineral element that functions as an important component of many enzyme systems, including those associated with nucleic acid synthesis and metabolism of proteins and carbohydrates, thus making it an essential nutrient for growth. The purpose of this study was to evaluate growth, carcass characteristics, and plasma urea nitrogen concentrations in finishing heifers supplemented with Optaflexx at 0 or 200 mg/animal daily, in the presence of 30 or 100 ppm supplemental zinc. We hypothesized that feeding Optaflexx could increase requirements for dietary zinc, and that additional zinc supplementation could increase the growth response to Optaflexx.
Keywords: feedlot cattle; Optaflexx; zinc sulfate